AN ANALYSIS ON TEACHING ENGLISH USING ENGLISH MOVIE AT THE EIGHT GRADE AT SMPN 3 TUNGKAL JAYA - Nurhasahah, Amalia; Hasanah, Dewi; Abadi, Ayuliamita; Santika, Giar (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2020)
The purpose of this research is to determine how instructors in class VIII.1 B SMPN 3 Tungkal Jaya teach English using English films. In this research, qualitative methodology was employed. Observation and interviews were employed to collect data for this research, whose subject is an eighth-grade English teacher at SMPN 3 Tungkal Jaya. This research revealed that teachers use three activities to teach English through films: pre-viewing, during viewing, and after viewing. By utilising these three activities, teachers can make it easier for students to learn English through films, as well as enhance students' listening, speaking, writing, and vocabulary abilities. After learning how to use films, teachers designate students homework so they can assess their comprehension.